A review of pathogens in selected Baltic Sea indicator species. (April 2020) - Sonne, Christian; Lakemeyer, Jan; Desforges, Jean-Pierre; Eulaers, Igor; Persson, Sara; Stokholm, Iben; Galatius, Anders; Gross, Stephanie; Gonnsen, Katharina; Lehnert, Kristina; Andersen-Ranberg, Emilie U.; Tange Olsen, Morten; et al.
Highlights: We review the of pathogens in select marine and terrestrial key species of the Baltic Sea. This review is the first to merge and present available information and baseline data for the Baltic Sea. Pathogens including parasites, bacteria and virus were reviewed. Abstract: Here we review the state-of-the-art of pathogens in select marine and terrestrial key species of the Baltic Sea, i.e. ringed seal ( Pusa hispida ), harbour seal ( Phoca vitulina ), grey seal ( Halichoerus grypus ), harbour porpoise ( Phocoena phocoena ), common eider ( Somateria mollissima ), pink-footed goose ( Anser brachyrhynchus ) and white-tailed eagle ( Haliaeetus albicilla ). This review is the first to merge and present available information and baseline data for the FP7 BONUS BaltHealth project: Baltic Sea multilevel health impacts on key species of anthropogenic hazardous substances . Understanding the spread, prevalence and effects of wildlife pathogens is important for the understanding of animal and ecosystem health, ecosystem function and services, as well as human exposure to zoonotic diseases. This review summarises the occurrence of parasites, viruses and bacteria over the past six decades, including severe outbreaks of Phocine Distemper Virus (PDV), the seroprevalence of Influenza A and the recent increase in seal parasites. We show that Baltic high trophic key species are exposed to multiple bacterial, viral and parasitic diseases. Parasites, such as C. semerme and P. truncatum present in the colon and liver Baltic grey seals, respectively, and anisakid nematodes require particular monitoring due to their effects on animal health. In addition, distribution of existing viral and bacterial pathogens, along with the emergence and spread of new pathogens, need to be monitored in order to assess the health status of key Baltic species. Relevant bacteria are Streptococcus spp., Brucella spp., Erysipelothrix rhusiopathiae, Mycoplasma spp. and Leptospira interrogans ; relevant viruses are influenza virus, distemper virus, pox virus and herpes virus. This is of special importance as some of the occurring pathogens are zoonotic and thus also pose a potential risk for human health. Marine mammal handlers, as well as civilians that by chance encounter marine mammals, need to be aware of this risk. It is therefore important to continue the monitoring of diseases affecting key Baltic species in order to assess their relationship to population dynamics and their potential threat to humans. These infectious agents are valuable indicators of host ecology and can act as bioindicators of distribution, migration, diet and behaviour of marine mammals and birds, as well as of climate change and changes in food web dynamics. In addition, infectious diseases are linked to pollutant exposure, overexploitation, immune suppression and subsequent inflammatory disease. Ultimately, these diseases affect the health of the entire ecosystem and, consequently, ecosystem function and services. As global warming is continuously increasing, the impact of global change on infectious disease patterns is important to monitor in Baltic key species in the future.